Ascites, a New Cause for Bilateral Hydronephrosis: Case Report - Deepika Jain; Smrita Dorairajan; Madhukar Misra (The Scientific World Journal)
Bilateral hydronephrosis secondary to urinary obstruction leads to a buildup of back pressure in the urinary tract and may lead to impairment of renal function. We present a case of a 57-year-old male with a history of alcoholic liver cirrhosis, who presented with tense ascites and acute renal failure. Bilateral hydronephrosis was seen on abdominal ultrasound. Multiple large-volume paracenteses resulted in resolution of hydronephrosis and prompt improvement in renal function.